2014
DOI: 10.5102/ucs.v12i1.2667
|View full text |Cite
|
Sign up to set email alerts
|

Resultados em curto prazo da reabilitação após cirurgia de reconstrução do ligamento cruzado anterior utilizando enxerto do tendão patelar contralateral

Abstract: Resultados em curto prazo de reabilitação após cirurgia de reconstrução de ligamento cruzado anterior utilizando-se enxerto de tendão patelar contralateral* Results in short term rehabilitation after surgery cruciate ligament reconstruction previous using patellar tendon graft contralateral Resumo As técnicas convencionais de cirurgia de reconstrução do LCA e os princípios que norteiam a reabilitação vêm surgindo como alternativas que proporcionam uma recuperação mais precoce e segura. O advento da utilização … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
1
Order By: Relevance
“…No Brasil, Oliveira et al (2014), Lobo et al (2018) e Ataídes et al (2013 demonstraram os resultados clínicos da recuperação em curto e médio prazo de pacientes operados e reabilitados sob as mesmas condições de Shelbourne (2006). Todos encontraram os pacientes satisfeitos do ponto de vista funcional, porém a avaliação isocinética demonstrou a presença de diferenças significativas no desempenho muscular entre os membros, na qual o doador se mostrava deficiente.…”
Section: Palavrasunclassified
“…No Brasil, Oliveira et al (2014), Lobo et al (2018) e Ataídes et al (2013 demonstraram os resultados clínicos da recuperação em curto e médio prazo de pacientes operados e reabilitados sob as mesmas condições de Shelbourne (2006). Todos encontraram os pacientes satisfeitos do ponto de vista funcional, porém a avaliação isocinética demonstrou a presença de diferenças significativas no desempenho muscular entre os membros, na qual o doador se mostrava deficiente.…”
Section: Palavrasunclassified
“…Figuras 10 e 11. Início da fisioterapia pós-operatória (Shelbourne, 2000(Shelbourne, , 2005(Shelbourne, , 2006Shelbourne et al, 2007;Biggs et al, 2009;Shelbourne et al, 2015 (Oliveira et al (2004(Oliveira et al ( , 2006(Oliveira et al ( , 2009(Oliveira et al ( , 2014, Lobo et al (2006Lobo et al ( , 2013Lobo et al ( , 2018…”
Section: Cálculo Amostralmentioning
confidence: 99%
“…Previous studies 6 , 30 , 36 demonstrated the clinical results of short- and medium-term recovery of patients who underwent ACL reconstruction with a contralateral bone–patellar tendon–bone (BPTB) graft and were rehabilitated under the same conditions as described by Shelbourne and Klotz. 45 The patients were satisfied with their function, but the isokinetic evaluation at multiple time points showed the presence of significant differences in muscle performance between each lower limb, of which the donor limb, (ie, the healthy limb), was shown to be more deficient.…”
mentioning
confidence: 97%
“…In general, the literature has been limited to understanding the ideal time to introduce resistance exercise, 5,18,28,49 measuring the loads generated during movements, comparing open and closed kinetic chain exercises, 14,25,40 and analyzing the progression of sensorimotor training (neuromuscular training). 41 Previous studies 6,30,36 demonstrated the clinical results of short-and medium-term recovery of patients who underwent ACL reconstruction with a contralateral bone-patellar tendon-bone (BPTB) graft and were rehabilitated under the same conditions as described by Shelbourne and Klotz. 45 The patients were satisfied with their function, but the isokinetic evaluation at multiple time points showed the presence of significant differences in muscle performance between each lower limb, of which the donor limb, (ie, the healthy limb), was shown to be more deficient.…”
mentioning
confidence: 98%
See 1 more Smart Citation